Congenital Urethrocutaneous Fistula: An Interesting Case. - AI, Roger; J, Anne Rachel (Department of Surgery, UKM Medical Centre, 2014)
A congenital urethrocutaneous fistula is a rare anomaly which was first described in 1962 by Gupta. Clinically, children present when their guardian is alarmed by either frequent urinary dribbling or unusual stream when they pass urine. This congenital anomaly can present in isolation or be accompanied by a chordee, hypospadia and anorectal malformations in a newborn. The surgical management will either be a primary repair of the fistula or converting it to a hypospadia before proceeding with a single or staged hypospadia repair. Surgical technique will depend on the local tissue factors and associated anomalies.